2015
DOI: 10.1186/s40199-015-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic effect of Allium cepa L. and quercetin in a murine model of Blomia tropicalis induced asthma

Abstract: BackgroundAsthma is an inflammatory condition characterized by airway hyperresponsiveness and chronic inflammation. The resolution of inflammation is an essential process to treat this condition. In this study we investigated the effect of Allium cepa L. extract (AcE) and quercetin (Qt) on cytokine and on smooth muscle contraction in vitro and its therapeutic potential in a murine model of asthma.MethodsAcE was obtained by maceration of Allium cepa L. and it was standardized in terms of quercetin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
70
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 52 publications
1
70
0
4
Order By: Relevance
“…26 Studies suggest that quercetin, an important flavonoid antioxidant thought to promote health, partly due to its ability to act as an antioxidant against ROS, helps in maintaining the blood pressure, fighting asthma and allergies, preventing angiocardiopathy and tumor progression, and so on. [27][28][29][30][31][32][33] Indeed, quercetin as a well-known flavonoid with various biological effects has been widely used in many disease models. However, the molecular mechanisms underlying the protective actions of quercetin against kidney injury in mice fed fat-rich diet are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Studies suggest that quercetin, an important flavonoid antioxidant thought to promote health, partly due to its ability to act as an antioxidant against ROS, helps in maintaining the blood pressure, fighting asthma and allergies, preventing angiocardiopathy and tumor progression, and so on. [27][28][29][30][31][32][33] Indeed, quercetin as a well-known flavonoid with various biological effects has been widely used in many disease models. However, the molecular mechanisms underlying the protective actions of quercetin against kidney injury in mice fed fat-rich diet are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin, an important antioxidant with various bioactivities, has been widely studied in a number of disease models, such as arteriosclerosis, diabetes, and cancer. [27][28][29][30][31][32][33] In this regard, it was found that GQ administration can downregulate HFD-induced kidney injury by suppression of proinflammatory cytokines and chemokines. Of note, insulin resistance, lipid metabolism dysfunction, and serum inflammatory cytokine increase were further inhibited by GQ treatment, suggesting that GQ restrained HFD-stimulated metabolic syndrome in a dose-dependent manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Allergic contact dermatitis or irritation and anemia were reported for A. cepa oil or its aqueous extract [11]. However, no toxic effect was observed in mice following the oral administration of 1,000 mg/kg body weight (BW)/day of A. cepa extract [10]. Moreover, no mutagenicity or oxidative DNA damage was induced by propyl propane thiosulfinate derived from organosulfur compounds isolated from A. cepa [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This plant acts as a booster of the immune system [8], and its effect on cytokines reflects its immunomodulatory property [9]. Anti-asthmatic properties of the extract of A. cepa and its constituent quercetin on cytokines, inflammatory cells, and smooth muscle contraction were shown in a murine model of asthma [10]. Allergic contact dermatitis or irritation and anemia were reported for A. cepa oil or its aqueous extract [11].…”
Section: Introductionmentioning
confidence: 99%